Imposter identification in low prevalence environments - Susa, Kyle J. (Legal and criminological psychology, 2019)
Purpose. Travel document screeners play an important role in international security when determining whether a photograph ID matches the tendering individual. Psychological research indicates when conditions involve low base rates of ‘imposter’ photographs, document screeners change their response criterion for rendering a ‘match’ determination. The primary purpose of the current experiments was to examine the nature of this base rate criterion shift, free from experimental bias, for both own- and other-race faces. Further, Experiment 2 examined how low-base rate conditions might moderate a cross-race effect in the calibration between confidence and accuracy. Method. In two experiments, participants completed an 80-trial task where they were asked to determine whether a passport photograph matched the photograph of a tendering individual. The base rate of imposter IDs and the race of the people in the photographs were manipulated across participants. Signal detection measures and the calibration between confidence and accuracy were analysed. Results. In each experiment, low base rates of imposter identifications induced a conservative criterion shift such that people were more likely to declare that faces ‘mismatch’. Further, race and imposter base rate interacted to influence the confidence–accuracy calibration, suggesting a cross-race effect on calibration was exacerbated in the low imposter base rate condition, and low-base rate conditions also elicited greater overconfidence for other-relative to own-race faces. Conclusions. Free from experimental bias, low imposter base rates induced a conservative response criterion, leading participants to render more ‘mismatch’ decisions. Moreover, low base rates moderated cross-race effects in the calibration between confidence and accuracy, and in a measure of overconfidence.